Nietzsche's philosophy of self-creation as practical philosophy: an understanding, and overcoming, of suffering as philosophical problem. - Kleingeld, Charl (Stellenbosch : Stellenbosch University, 2016)
Thesis (MA)--Stellenbosch University, 2016.